Kitsch, Camp, and Opera: Der Rosenkavalier - Le Tourneau, Gary (Canadian University Music Review / Revue de musique des universités canadiennes, 1994)
In her celebrated essay, "Notes on Camp," Susan Sontag identifies Richard Strauss’s most famous opera, Der Rosenkavalier as forming part of the canon of "camp." What is it about this work and its relationship to fin-de-siècle Vienna which gives it over to the "camp" aesthetic?In this article, the author examines the essence of the style known as camp, as derived from kitsch, another mode of "failed seriousness." Central to this investigation is the manner in which certain aesthetic objects can inhabit the realms of "high" or "serious" art and also that of popular culture. Hermann Broch, Theodor Adorno, and others suggest that kitsch is a parasitic ingredient in bourgeois culture and that this element can invade and "negate" an aesthetic object or experience. The historical imperatives found in romantic opera, bourgeois culture, and marginalized groups form an important element in defining the creations of modernist culture.Part of our understanding of what constitutes "serious" art has at its centre ways of maintaining autonomy and refusing the prospect of "negating" itself. One way of experiencing and examining those works which "refuse the burden of autonomy" is through the categories of questionable or marginal sensibilities, in this case: kitsch and camp.Der Rosenkavalier, with its fawning tribute to eighteenth-century Vienna, overt homage to Mozart, and its heralding of the composer's withdrawal from the avant-garde, proves to be a superb example of alternative sensibilities.